Aeromonas hydrophila Bivalen Vaccines to Improve Body Resistance catfish (Pangasius hypophthalmus) Against Attacks Motile Aeromonas Septicemia - Dwi Mailani; Fatmawati Fatmawati; Noor Arida Fauzana; Olga Olga (Jurnal Perikanan dan Kelautan, 2020)
Motile aeromonas septicemia/MAS diseases due to Aeromonas hydrophila infection is an obstacle in cultivation of catfish (Pangasius hypophthalmus). MAS control can be done by administering vaccines. The purpose of this research is to get the right and effective dose of bivalent vaccine for controlling MAS at catfish. Both isolates will be used as vaccines are local strains of A. hydrophila CASO.01.G and SBMI.2. Both of them were isolated from disease catfish in the aquaculture ponds in Cindai Alus and Sungai Batang villages, Banjar Regency, South Kalimantan. Vaccines are made by heating (heat killed) at 100oC for 60 minutes. A total of  13 test catfish measuring 9-13 cm were included in each aquarium. The design used was a completely randomized design with 5 treatments and 3 replications, namely bivalent vaccine with a dose of 109 cells/ml, 108 cells/ml, 107 cells/ml, 106 cells/ml, and control (PBS solution pH 7.0). The highest antibody titers in treatments vaccinated fish at a dose of 107 cells / ml (1,706.67). The effectiveness of the vaccine can be seen by the high RPS value of the treatment dose 109 cells/ml (97.22%); 108 cells/ml (100%); 107 cells/ml (97.22%); and 106 cells/ml (100%). The control MTD value was 1 day with 97.43% mortality, while in the vaccine treatment with dose of 107 cells/ml, there was a MTD repeat value for 1 day, but only 1 fish died. Water quality of this research are supportive and not a cause of fish death during the challenge test